P390 Methotrexate is not superior to placebo in maintaining remission in patients with ulcerative colitis: results from the MERIT-UC study. (16th January 2018) - Herfarth, H; Barnes, E L; Jackson, S; Valentine, J F; Hanson, J; Higgins, P D R; Isaacs, K L; Osterman, M T; Sands, B E; Lewis, J D; ,
Abstract: Background: Parenteral methotrexate (MTX) is effective in inducing and maintaining remission in patients with Crohn's disease. In the METEOR trial, MTX induced steroid-free clinical remission but not endoscopic healing in a significantly higher percentage of patients compared with placebo (P). We conducted a randomised, multicentre placebo-controlled trial to determine the efficacy and safety of MTX in maintaining steroid free remission in patients with moderately–severely active UC, who had responded and were able to discontinue steroids after open label induction with steroids and MTX. Methods: The 48-week trial comprised a 16 week open label induction period followed by a 32 week double-blind placebo-controlled maintenance period (MP). Patients with active UC (Mayo score 6–12 with endoscopy subscore ≥2) despite previous conventional or anti-TNF therapy were included and treated with open label MTX 25 mg/week sc and a 12 week steroid taper. At week 16, responders, defined as a decrease of the clinical Mayo score to ≤5 and steroid free since week 12, were randomly assigned to either continue MTX 25 mg/week or P until week 48. All patients received 2.4 g mesalamine daily. We compared the efficacy of treatment by analysing the proportion of patients who remained relapse-free during MP defined by a clinical Mayo score ≤2 at week 32 without increase ≥3 points during MP and no use of steroids or other medications to control disease activity during MP. We evaluated faecal calprotectin levels at screening, week 16 and week 48. Results: Fifty-one percent (91/179) of patients responded and 30% (53/179) achieved remission at week 16. Of 91 patients with steroid free response, 7 patients declined randomisation and 84 patients were randomised in the P controlled MP. In the P and MTX arm, 63% (25/40) and 66% (29/44) of patients experienced a relapse ( p = 0.75) (Figure 1). Of the patients without relapse at week 48, 75% (12/16) and 85% (12/15) of patients on P and MTX, respectively, were in steroid-free clinical remission. There were no significant differences comparing relapse rates based on different calprotectin levels at week 16 or failed previous therapies before entry in the trial. Nausea was numerically more common with MTX. No new safety signals were detected. Conclusions: Although when combined with a standardised steroid taper, parenteral MTX 25 mg/week induced a steroid free response and remission rate in a substantial proportion of pat. with active UC, it was not superior to P in preventing relapse of disease. Thus, MTX does not represent a therapeutic option for long-term maintenance of remission in pat. with UC.